2019
DOI: 10.1101/828889
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Motor imagery practice during arm-immobilization benefits sensorimotor cortical functions and plasticity-related sleep features

Abstract: Motor imagery (MI) is known to engage motor networks and could compensate for the maladaptive neuroplasticity elicited by immobilization. This hypothesis and associated underlying neural mechanisms remain underexplored. Here, we investigated how MI practice during 11 h of arm-immobilization influences sensorimotor and cortical representations of the hands, as well as sleep. Fourteen participants were first tested after a normal day, followed by two 11-h periods of immobilization, either with concomitant MI tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Further, EMS could trigger motor imagery during sleep, which likewise has been associated with enhanced motor learning (e.g., in lucid dreams, Schädlich et al, 2017 ). In one recent study, Debarnot, Perrault, Sterpenich, Legendre, Huber, Guillot, and Schwartz (2019) found that waking motor imagery practice during arm immobilization led to increased subsequent REM sleep and improved adaptation the next day. The use of EMS to augment motor dream imagery thus offers an intriguing application of dream engineering for physical rehabilitation.…”
Section: Simulating Worlds Through Sensory Stimulationmentioning
confidence: 99%
“…Further, EMS could trigger motor imagery during sleep, which likewise has been associated with enhanced motor learning (e.g., in lucid dreams, Schädlich et al, 2017 ). In one recent study, Debarnot, Perrault, Sterpenich, Legendre, Huber, Guillot, and Schwartz (2019) found that waking motor imagery practice during arm immobilization led to increased subsequent REM sleep and improved adaptation the next day. The use of EMS to augment motor dream imagery thus offers an intriguing application of dream engineering for physical rehabilitation.…”
Section: Simulating Worlds Through Sensory Stimulationmentioning
confidence: 99%